1997
DOI: 10.1203/00006450-199703000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Metabolism in Very Low Birth Weight Infants

Abstract: To quantitate glutamine kinetics in premature infants and determine whether glutamine affects leucine metabolism. 11 very low birth weight (< 1250 g) neonates received 4-h i.v. infusions of L-[2H3]leucine and L-[13C5]glutamine, along with orogastric infusion of L-[I-13C]leucine and L-[I-13C]glutamine on the 10th d of life and in the fed state. Patients were receiving parenteral nutrition and were randomized to receive either hypocaloric, enteral preterm formula alone (controls; n = 5), or glutamine (0.2 g.kg-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 14 publications
6
31
0
2
Order By: Relevance
“…This result is consistent with our earlier studies: in another group of VLBW infants, enteral glutamine delivery was associated with a trend toward a reduction in B Leu ; in that previous study, the approximately 16% decline, however, failed to reach statistical significance (24). Besides a type II statistical error, several differences in study design can, however, account for the difference: in that earlier study, glutamine was supplied via the enteral route, and the dose was only 40% of that used in the current study (0.2 versus 0.5 g · kg Ϫ1 · d Ϫ1 ).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This result is consistent with our earlier studies: in another group of VLBW infants, enteral glutamine delivery was associated with a trend toward a reduction in B Leu ; in that previous study, the approximately 16% decline, however, failed to reach statistical significance (24). Besides a type II statistical error, several differences in study design can, however, account for the difference: in that earlier study, glutamine was supplied via the enteral route, and the dose was only 40% of that used in the current study (0.2 versus 0.5 g · kg Ϫ1 · d Ϫ1 ).…”
supporting
confidence: 82%
“…This is, however, unlikely as 1) proteolysis seems to be somehow insulin resistant in neonates (26), and amino acids may be the main factor regulating proteolysis in the neonatal period; and 2) moreover, although insulin levels were not measured in the present study, we failed to observe any rise in insulin secretion in healthy adults given large oral doses of glutamine in previous studies [(11), and Darmaun et al unpublished personal results]. In earlier studies, we found glutamine utilization rate and metabolic clearance rate (glutamine utilization rate divided by plasma glutamine concentration) to be much higher in VLBW infants than older children (24). The higher clearance rate of plasma glutamine may point to a greater glutamine requirement in VLBW infants.…”
mentioning
confidence: 74%
“…Dietary digested amino acids can be used for intestinal energy generation; for conversion via transamination into other amino acids, metabolic substrates, and biosynthetic intermediates; and for tissue growth. Previous studies in neonates showed a considerable intestinal amino acid metabolism, with some amino acids that are extensively catabolized, while others are presumed to be incorporated to a great extend in mucosal cellular or excreted (glyco-)proteins (5)(6)(7)(8)(9).…”
Section: (Pediatr Res 67: 194-199 2010)mentioning
confidence: 99%
“…In human adults, Matthews et al (15,16) found that the splanchnic extraction of glutamine was 60 to 80% of the dietary intake, of which oxidation was a major metabolic fate. In preterm infants, Darmaun et al (5) showed that glutamine is extensively extracted from the enteral lumen. Whether preterm infants sequester and oxidize the same amount of dietary glutamine has not yet been investigated.…”
Section: (Pediatr Res 67: 194-199 2010)mentioning
confidence: 99%
“…Esses resultados sugerem que a glutamina administrada, via enteral, foi completamente metabolizada pelo intestino e, portanto, não atingiu a circulação sangüínea (Parimi et al, 2004). Não obstante, em outro estudo (Darmaun et al, 1997), apenas cerca de 46% da glutamina administrada junto à nutrição enteral (0,2 g/kg/dia) foram extraídas pelo intestino durante o processo de absorção em neonatos PT e com BPN com 10 dias de vida.…”
Section: Suplementação Enteral Com Glutaminaunclassified